2016
DOI: 10.1515/tvsb-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rolling Resistance in Dem Models With Spherical Bodies

Abstract: The rolling resistance is an artificial moment arising on the contact of two discrete elements which mimics resistance of two grains of complex shape in contact rolling relatively to each other. The paper investigates the influence of rolling resistance on behaviour of an assembly of spherical discrete elements. Besides the resistance to rolling, the contacts between spherical particles obey the Hertzian law in normal straining and Coulomb model of friction in shear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The geometry of the bed has been selected according to [13], which is a cylindrical crucible with diameter of 20 mm and height of 18 mm in order to validate the numerical data.…”
Section: Simulation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry of the bed has been selected according to [13], which is a cylindrical crucible with diameter of 20 mm and height of 18 mm in order to validate the numerical data.…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…One of the parameters that affects the accuracy of the DEM simulations for generating packed beds of particles is rolling friction between the particles and the particles and the wall. Rolling friction is a moment-induced to the contact point between two discrete elements that could mimic the rolling behavior of two complex shaped particles [13][14][15]. Goniva et al [16] showed that the CFD-DEM simulations results would be improved to a great extent only by applying a proper rolling friction model.…”
Section: Introductionmentioning
confidence: 99%